Using Chatbots to Compare Drug Prices Extracted in Real-Time from the WEB - Avila, Caio Viktor S.; Vidal, Vania P.; Caldas, Asley; Rolim, Tulio V.; Lavor, Thays (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2019)
In this paper we present a chatbot for the medicines information consultation. The system presented aims to act as a single access point for the natural and simplified information retrieval of medicines, its prices and risks, democratizing the access to knowledge and promoting the conscious consumption of medicines. The chatbot has two modes of operation: Quick Response and Interactive modes. The first answers questions asked in natural language, while the second has three interactive tasks, namely Navigation, Query and Price Comparison. In this work, we focus on the presentation of the system architecture and the Price Comparison task. This task presents the best prices for medicines and their best possible substitutes extracted in real-time from web with the help of information obtained from a linked data mashup. The work is still under development, however in this paper we present the results of preliminary assessments and possible directions for future work.